O ensino de ciências naturais nos anos iniciais: concepções e práticas pedagógicas dos docentes em formação pelo PARFOR/Pedagogia/UFPA - OLIVEIRA, Sônia Maria Maia (Universidade Federal do Pará, 2015)
The study had as main objective to understand the Teaching of Natural Sciences in public schools in the metropolitan area of Belem from the conceptions and pedagogical practices of teachers in training at PARFOR working in the early years of elementary school. The specific objective are summarized in analyzing the concepts of natural science teachers in training who work in the early years; describe the pedagogical practices that are adopted by professors to teach Natural Sciences and assess whether there is influence of the National Curriculum Parameters of Natural Sciences in the design and pedagogical practice adopted by these teachers in training (who are students of PARFOR / UFPA). As object of study, focused on public school in Science Teaching in the metropolitan area of Belem from the perspective of teachers in training at the Faculty of Education of the UFPA. This is a qualitative research. The data collection technique was done by means of document analysis and field, whose sample of 20 teachers from public schools, who are currently in training at the PARFOR Degree in Bethlehem Pa-Campus Pedagogy. During data collection, we used official documents such as the NCP of Natural Sciences, Management Report PARFOR / UFPA and the Pedagogical Political Project of the Education Course / PARFOR. It was applied a questionnaire with open and closed questions to investigate the variables: socioeconomic, vocational training, labor market, conceptions of science and pedagogical practices. Adopted the content analysis data. Finally, in the final considerations spoke on the central and relevant aspects of the research, presenting the results and most significant analysis. The locus of research took place at the Institute of Educational Sciences - Faculty of Education - Campus Silveira Neto - Belem, Para Brazil. It is believed that this study will subsidize other research on science education in the early years, as in the databases of indexed events and magazines of the area, yet there is no work that report to this issue here in the state of Para. You can also serve as a source of research for other studies that arise in the line of Education: Curriculum, Epistemology and History.